NILAI-NILAI GOTONG ROYONG DALAM TRADISI SIHALI AEK PADA MASYARAKAT TOBA DI HUMBANG HASUNDUTAN - harvina vina lubis (Kementerian Pendidikan dan Kebudayaan, 2020)
ABSTRACTSihali Aek is a tradition of cleaning water ropes as part of the management of water sources to be used as well as possible for the lives of the community in irrigating rice fields. This research aims to examine the values of mutual cooperation in the Sihali Aek tradition. To explain the values of mutual cooperation in the Sihali Aek tradition, a qualitative method is used with data collection techniques through observation, interviews, and literature study. The Sihali Aek tradition is an annual tradition that is carried out in October each year. October is considered the right time to welcome the entry of the rainy season and the preparation of the planting season for paddy fields. Before the rice planting season, first ensure that water is available properly, because rice needs water for its growing period. Therefore, Sihali Aek is a very important activity for the people who are mostly farmers. Sihali Aek tradition contains wisdom in a variety of wisdom in the form of mutual cooperation values.